Complete resection of local advanced thymic carcinoma with total aortic arch replacement after chemotherapy: a case report - Hidenori Kuno; Soichiro Funaki; Kenji Kimura; Kazuo Shimamura; Keiwa Kin; Toru Kuratani; Yoshiki Sawa; Yasushi Shintani (Surgical Case Reports)
Abstract Background Although complete surgical resection of thymic carcinoma is a prognostic factor, it is not always an option for advanced tumors because of locoregional invasion. Extended surgery combined with a major blood vessel procedure remains controversial because of the increased risk of mortality. Case presentation Chest computed tomography (CT) uncovered an abnormal shadow in the mediastinum of a 74-year-old man. An irregularly shaped tumor obstructed the left innominate vein, and invasion of the aortic arch was suspected. A CT-guided percutaneous needle biopsy revealed squamous cell carcinoma of the thymus, which was considered unresectable. The patient underwent chemotherapy elsewhere, then was referred to us for surgical resection. We combined extended surgery with total aortic arch replacement under a cardiopulmonary bypass. Complete resection was achieved, and the patient remains alive without recurrence at 3 years after surgery Conclusion Resection including aortic arch replacement might be an option that can achieve complete resection of local advanced thymic carcinoma.